2012 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--21949
|View full text |Cite
|
Sign up to set email alerts
|

Student Software Engineering Learning via Participation in Humanitarian FOSS Projects

Abstract: is Chair and Associate Professor in the Computer Science and Information Technology Department at Western New England College. She has a long-time interest in software engineering education and most recently has received NSF funding to investigate the use of humanitarian free and open source software to educate computing students. She is also currently participating in an NIH grant for developing database-driven software for biological NMR analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These results are aligned with prior investigations, such as the one conducted by Nascimento et al [7], which found that 90% of the students who participated in an open-source project-based learning course had a similar experience to what they can find in the industry. In addition, in the study by Ellis et al [24], the students somewhat agreed (mean score of 3.6 out of 5) that they improved their understanding of how to behave like a computing professional through their participation in a Humanitarian Free and Open Source Software project. The instructors also considered that the students acquired new useful knowledge (IQ2, median = 5.0, mode = 5).…”
Section: Learning Experiencementioning
confidence: 90%
See 2 more Smart Citations
“…These results are aligned with prior investigations, such as the one conducted by Nascimento et al [7], which found that 90% of the students who participated in an open-source project-based learning course had a similar experience to what they can find in the industry. In addition, in the study by Ellis et al [24], the students somewhat agreed (mean score of 3.6 out of 5) that they improved their understanding of how to behave like a computing professional through their participation in a Humanitarian Free and Open Source Software project. The instructors also considered that the students acquired new useful knowledge (IQ2, median = 5.0, mode = 5).…”
Section: Learning Experiencementioning
confidence: 90%
“…Some studies describe real experiences of applying open-source projects in academic courses. Researches such as the ones conducted by Ellis et al [13,24] analyze the impact of learning activities with Humanitarian Free and Open Source Software (HFOSS) projects in terms of motivation, learning experience, and career plans. Other studies describe courses where students take different roles (e.g., developers, testers, requirements definition engineers) in real open source project developments [7,19,25].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation